Photoconductivity of the Polymer Layer with Resazurin Sodium at Two-photon Excitation - T.M. Sakun (Журнал нано- та електронної фізики)
Experimental and theoretical studies of the photoconductivity of the polymer layer (PVP) with resazurin solution at two-photon excitation revealed that the two-quantum excitation in T(*)- state which corresponds to the quantum transition from a deep -MO on the free *-MO is the cause of the two processes: the electron transfer from the matrix to the dye molecule and dissociation of the dye molecules with the release of oxygen anion. Two-quantum excitation of the molecules in the triplet state which is lower than said T(*)- state prevents dissociation of the molecule, however, significantly increases the acceptor dye properties, enabling electron transfer from the matrix to the photoconductive dye and a hole matrix. The resulting radical anion dye eventually gives extra electron matrix, where it can recombine with a hole or captured by the trap.